Automated Myth and the Postsocialist Digital State: The Imperial Trick of the Kratt AI Initiative in Estonia - Atanasoski, Neda; Koobak, Redi (Imaginations)

(untitled) (York University, 2026)
This article examines Estonia’s Kratt AI initiative as a model for automating government services with AI systems. Responding to the state’s naming of these systems after the kratt—a mythic servant that turns on its master when left idle—the article advances the concept of “automated myth”: folklore embedded in AI to naturalize links between technological progress and liberal democracy. In Estonia, this myth performs an imperial trick, indigenizing technofutures as national heritage while obscuring the imperiality of Silicon Valley capitalism that has shaped postsocialist transformations of the e-republic. It shows how policy branding and interfaces shape the cultural and political landscapes of AI governance.